Why Was the Official Australian Monsoon Onset Unusually Late in 2024/25? - Tim Cowan; Rajashree Naha; Hanh Nguyen; Hanna Heidemann; Sugata Narsey; Matthew C. Wheeler; Corey Robinson; Chris Lucas; Andrew G. Marshall; Lin Wang (Advances in Atmospheric Sciences, 2026)
The official 2024/25 Australian summer monsoon (ASM) onset occurred on 7 February, more than two weeks later than the previous record. Defined using Darwin winds, the official ASM typically arrives between mid-December and mid-January. Here, we investigate (1) why the ASM onset was record late, despite La Niña-like conditions, and (2) if the late ASM onset was consistent with other unofficial monsoon and rainy season onset definitions. Our results show earlier onsets when using wind and rainfall-based definitions, mainly due to strong synoptic-to-intraseasonal variability. Two onset definitions were triggered in December 2024 when the Madden–Julian Oscillation (MJO) contributed to deep convection and above-average rain over northern Australia. In late January, a monsoon trough formed over northeast and northwest Australia, but not over Darwin. With the MJO in a suppressed state, the Darwin region experienced record-breaking January temperatures. The ASM eventually arrived in early February, with the reason behind its historically late onset likely a result of weather noise and variability. Another location, ∼1200 km east of Darwin, did not experience such a late onset, using similar definitions. Relevant to monsoon systems globally, our study highlights the limitations of local onset or wind-only definitions, which may not necessarily capture the large-scale monsoonal conditions, and be amplified by short-term weather variability.

The 2024 Asian–Australian Monsoon Year: Widespread Extremes with Notable Subseasonal Variability and Socioeconomic Impacts - Lin Wang; Zizhen Dong; Tim Cowan; Peng Hu; Shiromani Jayawardena; Maheswar Pradhan; Hui Su; Thea Turkington; Wei Gu; Seok-Woo Son; Donaldi Sukma Permana; Rajashree Naha; et al. (Journal of Meteorological Research, 2026)

Exploring the green break of season and green date over northern Australia - Rajashree Naha; Tim Cowan; Matthew C. Wheeler; Jyoteshna Owens; David Cobon; Chelsea Jarvis; Peter O’Reagain (Agricultural Systems, 2026)

A Tale of Two Tails: Untangling the Phylogeography and Demographic History of Extant Species of Mulgara ( Dasycercus spp.) in the Australian Arid Zone - Aline Gibson Vega; Brenton von Takach; Linette Umbrello; Dympna Cullen; Mark Cowan; Helen Crisp; Chris Dickman; Tim Doherty; William La Marca; Jenny Molyneux; Colleen Sims; Peter B. S. Spencer; et al. (Journal of Biogeography, 2025)
Aim Australia's arid and semi‐arid zones cover about 70% of the continent, yet our understanding of the biogeography of these diverse and expansive landscapes remains limited. Mulgara ( Dasycercus spp.; Marsupialia: Dasyuridae), a widely distributed mammal taxon, offers an opportunity to explore patterns of the population structure across the region, previously hampered by taxonomic confusion surrounding extant species. Here, we aimed to (1) clarify the current distribution of extant Dasycercus lineages, (2) describe the population genomic structure of the widespread brush‐tailed mulgara, and (3) determine whether observed patterns of population genomic structure in brush‐tailed mulgara are consistent with biogeographic breaks. Location Arid and semi‐arid regions of Australia. Taxon Two species are extant; the brush‐tailed mulgara ( D. blythi ) and the crest‐tailed mulgara ( D. hillieri , previously D. cristicauda ). Methods We sampled individuals from contemporary and museum tissue collections, obtaining next‐generation sequencing data for 311 individuals, retaining 4360 single‐nucleotide polymorphisms (SNPs) for population genomic analysis. Results We found that the two extant species are clearly delineated, corresponding well to current understanding of their respective distributions. The population genomic substructure in the brush‐tailed mulgara (211 samples, 2740 SNPs) aligns primarily with major drainage divisions. Inference of historical population size change indicated that all populations have likely had stable population sizes for much of the past 1000 years, although post‐European colonisation declines in some populations cannot be ruled out. The Pilbara population was most differentiated from other populations and displayed a stronger pattern of isolation‐by‐distance. Nevertheless, observed heterozygosity was similar across each of the populations ( H o = 0.078–0.090). Conclusions Stable population dynamics linked to the ecology of the mulgara and their high dispersal potential likely explain consistent levels of genetic diversity across most populations, but the effects of geography, such as major drainage divisions, drive the apparent contemporary population structure. Additional targeted tissue collection in under‐sampled regions is recommended to better quantify genomic diversity, structure, and genetic health across the species' full range.

Seasonal climate forecast-an important tool in managing the risk of extreme weather events in Australia's wheat industry - Qunying Luo; Li Wen; Tim Cowan; Dale Schilling (Agricultural and Forest Meteorology, 2024)

Corrigendum to “Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate” [Agricultural Systems 214 (2024) 1–13/103838] - Duc-Anh An-Vo; David Cobon; Jyoteshna Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Statistical relationships between the Interdecadal Pacific Oscillation and El Niño–Southern Oscillation - Hanna Heidemann; Tim Cowan; Scott B. Power; Benjamin J. Henley (Climate Dynamics, 2024)
The climate of the Pacific Ocean varies on interannual, decadal, and longer timescales. This variability is dominated by the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), both of which have profound impacts on countries within and well beyond the Pacific. To date, previous studies have only examined a small subset of the possible links between ENSO, its diversity, and the IPO. Here we focus on the statistical relationship between decadal variability in ENSO properties and the IPO, testing the null hypothesis that the IPO arises from random decadal changes in ENSO activity, including ENSO diversity. We use observed sea surface temperature (SST) records since 1920 to investigate how the timing, structure, frequency, duration, and magnitude of El Niño and La Niña events differ between IPO phases. We find that using the relative frequency of El Niño and La Niña events and either the mean event duration or SST magnitude can reproduce up to 60% of the IPO Tripole Index timeseries. While the spatial SST patterns that represent the IPO and ENSO are similar, the IPO is meridionally broader in the central to eastern Pacific, which may be caused by a lagged relationship with low-frequency SST variability in the equatorial Pacific. In addition, North Pacific SST anomalies of opposite sign to the tropical Pacific SST anomalies is a unique feature of the IPO that cannot be explained by decadal ENSO variability. This suggests a clear IPO and ENSO relationship, but also independence in some of the IPO’s characteristics.

Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate - Duc-Anh An-Vo; David Cobon; Jo Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Circulation analogues and uncertainty in the time-evolution of extreme event probabilities: evidence from the 1947 Central European heatwave - Luke J. Harrington; Friederike E. L. Otto; Tim Cowan; Gabriele C. Hegerl (Climate Dynamics, 2019)

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

Large scale and sub-regional connections in the lead up to summer heat wave and extreme rainfall events in eastern Australia - Ghyslaine Boschat; Alexandre Pezza; Ian Simmonds; Sarah Perkins; Tim Cowan; Ariaan Purich (Climate Dynamics, 2015)

Annual sea surface temperature lag as an indicator of regional climate variability - Chung‐Leong Li; John A.T. Bye; Stephen J. Gallagher; Tim Cowan (International Journal of Climatology, 2013)
The annual SST lag for the world ocean is obtained from a Fourier analysis of the HadISST (1870–2008) and NOAA WOA05 (1900–2005) monthly SST data series. The main properties are a mean of 73 days and a standard deviation of 16 days, with tongues of high SST lag extending poleward and eastward from the equatorial regions where a maximum in lag of about 110 days occurs. The SST lag is the sum of an atmospheric surface heat flux lag and an ocean heat storage lag which is the dominant contributor and provides direct estimates of the damping time for air/sea heat exchange, which are in good agreement with observations in the eastern North Atlantic Ocean, and also predictions of the phase lag of the mid‐latitude ocean surface temperature field to El Nino‐Southern Oscillation (ENSO) forcing. Hence, SST lag can be used to diagnose global climate variability. Local differences in lag of up to about 15 days occur between the 1991–2005 and 1976–1990 periods, which are accompanied by significant changes in regional climate. The lag time series for grid points in the eastern Indian Ocean, North Pacific Ocean and North Atlantic Ocean show that the variability can be interpreted in terms of bounded random walks of length about 20 years. The CSIRO Mk. 3.5 run for Scenario A2 over the period 1871–2100 has a similar random structure and also shows a secular increase in SST lag in the temperate oceans which is attributable to an expansion of the tropical belt.

Crops that feed the world 9. Oats- a cereal crop for human and livestock feed with industrial applications - Athole Marshall; Sandy Cowan; Simon Edwards; Irene Griffiths; Catherine Howarth; Tim Langdon; Ethel White (Food Security, 2013)

Optimal motor control may mask sensory dynamics - Sean G. Carver; Tim Kiemel; Noah J. Cowan; John J. Jeka (Biological Cybernetics, 2009)